The Influence Of Transformational Leadership Style, Work Motivation, And Work Discipline On The Performance Of Employees Of RSUD Mojokerto District - Uripan, Koen Irianto; Mahendra, Angga Martha (International Humanity Advance, Business & Sciences, 2025)
In the era of Industry 4.0, the competition among companies has become increasingly fierce, prompting organizations to strive to maintain and develop themselves to achieve success. One of the key factors supporting the sustainability and development of an organization is human resources, which serve as a benchmark for success to achieve organizational goals. Using SPSS data analysis techniques with a path analysis approach, correlation tests, determination tests, simultaneous tests, and partial tests with a sample size of 75 employees, the results of this study show that leadership style, motivation, and work discipline significantly influence employee performance. Partially, only work discipline has a positive and significant effect on employee performance, while leadership style and motivation do not significantly influence employee performance but positively impact it. Furthermore, this study finds that work discipline has the most substantial influence on employee performance. The research used a saturated sample, which includes the entire population of 50 respondents. The quantitative method was applied, and the analysis used multiple linear regression, T-tests, F-tests, and classical assumption tests using SPSS version 25. The questionnaire employed in this research has been validated and tested for reliability. Based on the findings, transformational leadership style significantly influences employee performance, along with work motivation and employee discipline.